Eucharist and ecclesiology : essays in honor of Dr. Everett Ferguson - Willis, Wendell; Ferguson, Everett, 1933- (Pickwick Publications, 2016)
In the late twentieth century and since, ecumenical discussions on the nature and unity of the church have often centered on the Eucharist. This book is focused on that intersection of church and Eucharist in current Christian relationships. In the first part of the book representatives of the Orthodox tradition (Paul Meyendorff), the Roman Catholic tradition (Denis Farkasfalvy), and the Protestant tradition (Gary Badcock) discuss the relationship of Eucharist and church. These essays are followed by an overview and response to these theme essays by Everett Ferguson, who has published often on the topics. The second part of the book contains essays on particular issues important for understanding the Eucharist and Christian faith. These essays also come from the three theological traditions of the featured essays but focus on more specific issues behind the larger discussion. The essays address the New Testament texts on Eucharist and important later Christian writers. This book will be of value to scholars studying the Eucharist in the New Testament and the early Christian church, as well as to clergy who need to instruct congregations on the ecumenical discussions of the Eucharist.